(untitled) (Comprehensive Journal of Science, 2025)
This study aimed to analyze the impact of time management on productivity in governmental institutions, through a field study conducted at Libyan Telecommunications Company. The descriptive-analytical approach was adopted, and a questionnaire was used as the main data collection tool on a sample of (90) employees. The results showed that the level of time management practices was acceptable, while productivity levels were relatively high. The study revealed a positive and statistically significant correlation between time management and productivity, indicating that effective planning, organizing time, and prioritizing tasks contribute to improving institutional performance. The findings also indicated no statistically significant differences in time management or productivity attributable to gender or educational qualification, while differences were found according to years of experience and job position. The study concluded that time management represents an effective administrative approach for enhancing productivity in governmental institutions.